Temporomandibular disorders. Part 5: surgical management. (2nd September 2022) - Crawford, Charles; Foster-Thomas, Emma; Oluwajana, Funmi; Clarke, Peter; James, Martin; Khandavilli, Sunil; Kalantzis, Athanasios
Abstract : The temporomandibular joint (TMJ) is a complex arrangement with high functional requirements. Surgery is therefore only considered when conservative management has not been successful. Surgery may not always benefit and carries the risk of the condition worsening. There is a range of techniques available to the surgeon. The most commonly used is arthrocentesis and this is also the least invasive. The end-stage option for patients is total joint replacement. Whichever surgery the patient has received, it is likely that they will be in need of careful management by the primary care team for their continuing care. This article, the fifth in a series of six, outlines the scope of TMJ surgery. CPD/Clinical Relevance: A range of techniques is available for TMJ surgery, and many post-surgery patients will require routine dental management in the primary care setting.